Pengaruh Kualitas Layanan dan Inovasi Produk terhadap Kepuasan Pengunjung Wisata Boonpring Kabupaten Malang - surya angaraputra; ainul mufarichah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The development of the tourism sector requires destination managers to enhance visitor satisfaction through consistent service quality and sustainable product innovation. Boonpring Tourism Destination in Malang Regency, as a nature-based tourism attraction, needs to ensure that its services and tourism products are able to meet visitors’ expectations. This study aims to analyze the effect of service quality and product innovation on visitor satisfaction at Boonpring Tourism Destination, Malang Regency. This research employed a quantitative approach with a cross-sectional design. Data were collected through questionnaires distributed to 150 visitors who visited the destination in August 2025. Data analysis was conducted using simple linear regression with the assistance of SPSS software. The results indicate that service quality and product innovation have a positive and significant effect on visitor satisfaction, both partially and simultaneously. These findings suggest that consistent improvement in service quality and continuous development of tourism product innovation play a crucial role in shaping visitor satisfaction. The implications of this study are expected to serve as a reference for tourism managers in formulating strategies to enhance service quality and product innovation in order to improve competitiveness and ensure the sustainability of tourism destinations.